364 Management of benign metastasizing leiomyoma: a report of three cases. (13th November 2020) - Inoue, K; Yamaguchi, M; Ueda, T; Isono, R; Takimoto, Y; Tsubamoto, H; Shibahara, H
Abstract : Benign metastasizing leiomyoma (BML) is a rare disease associated with a history of uterine surgery leiomyomas. BML is often seen in the lungs. Symptomatic patients with BML are usually treated with surgical resection or medical castration. Here, we report three patients diagnosed with BML. A 58-year-old patient presented with back pain. Magnetic resonance imaging (MRI) and positron emission tomography – computed tomography (PET/CT) showed a tumor of 3 cm in diameter in the L2/L3 vertebrae with Fluorine-18 deoxyglucose (FDG) accumulation. Histopathology of CT-guided biopsy was smooth muscle tumor, which was compatible with the specimen obtained by hysterectomy for leiomyoma five years before. After administration of letrozole for one month, her back pain improved. Letrozole was used for 5 years, and the size of the tumor remained stable. A 38-year-old patient presented with abdominal distension. CT demonstrated multiple abdominal and subcutaneous tumors and uterine leiomyomas. She had myomectomy and complete surgical resection of the multiple tumor, and was diagnosed with BML. Six years later, she presented with slight cough, and CT showed multiple small nodules in the lungs. Because her symptom diminished spontaneously, she was followed without treatment. Her lung tumors gradually increased without symptoms. A 45-year-old patient with a past history of myomectomy twice presented with Raynaud symptom. CT showed multiple small nodules in the lung which showed no accumulation of 18-FDG. Histopathology of CT-guided biopsy was well-differentiated smooth muscle tumors, and she was diagnosed with BML. Because she had no symptoms, she was followed conservatively without treatment.